Implementing NIH Behavior Change Consortium Treatment Fidelity Recommendations in a Multi-Site Randomized Controlled Trial of an Active Music Engagement Intervention for Young Children with Cancer and Parents. (December 2022) - MacLean, Jessica A.; Stegenga, Kristin A.; Henley, Amanda K.; Robb, Sheri L.
Treatment fidelity is the use of methodological strategies to monitor and enhance reliability and validity of behavioral intervention trials. Despite availability of guidelines and checklists, treatment fidelity remains underreported, hindering evaluation, interpretation, and cross-study comparisons. Treatment fidelity is particularly important for music interventions given the inherent complexity of musical stimuli and flexibility required for tailored delivery. The purpose of this paper is to define and describe treatment fidelity strategies for our trial of a music-based play intervention for young children with cancer and parents grounded in the NIH Behavior Change Consortium Treatment Fidelity Recommendations. We report strategies for all 5 areas: study design, training providers, delivery of treatment, receipt of treatment, and enactment of treatment skills. We also discuss 4 challenges our team encountered, including: (1) standardizing live music delivery, (2) defining boundaries for tailored intervention delivery, (3) managing extended time between participants, and (4) minimizing risk for bias. This paper expands on current fidelity literature and may provide a working model for other investigators examining dyadic and/or active music interventions.